2016
DOI: 10.1186/s13550-016-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary perfusion by SPECT imaging using an endothelial cell tracer in supine humans and dogs

Abstract: BackgroundPulmonary perfusion is not spatially homogeneously distributed, and its variations could be of diagnostic value in lung vascular disease. PulmoBind is a ligand of the adrenomedullin receptor densely expressed in endothelial cells of lung capillaries. The aim of this study was to evaluate spatial distribution of human lung perfusion by using this novel molecular tracer of the pulmonary vascular endothelium.MethodsNormal humans (n = 19) enrolled into the PulmoBind phase I trial were studied (Clinicaltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The limited anatomical resolution of SPECT imaging in rodents with small lungs hampers precise evaluation of the distribution of 99m Tc-PulmoBind and the detection of heterogeneity of distribution. In a larger animals (dog) and in humans, we showed that 99m Tc-PulmoBind lung distribution follows gravitational and non-gravitational gradients in normal conditions that are modified by pathology [ 18 ]. Furthermore, in humans with group I PH, we derived a “heterogeneity perfusion index” and showed its utility in quantifying abnormal distribution of 99m Tc-PulmoBind in these subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limited anatomical resolution of SPECT imaging in rodents with small lungs hampers precise evaluation of the distribution of 99m Tc-PulmoBind and the detection of heterogeneity of distribution. In a larger animals (dog) and in humans, we showed that 99m Tc-PulmoBind lung distribution follows gravitational and non-gravitational gradients in normal conditions that are modified by pathology [ 18 ]. Furthermore, in humans with group I PH, we derived a “heterogeneity perfusion index” and showed its utility in quantifying abnormal distribution of 99m Tc-PulmoBind in these subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%